CONTRASTIVE MEANINGS OF THE ADJECTIVE "COLD" IN JAPANESE AND JAVANESE - Azizia Freda Savana (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
This study offers a comparative semantic examination of the Japanese cold-related adjectives samui and tsumetai with their Javanese equivalents adhem, atis, and anyep. The study used a qualitative descriptive method within a contrastive analytic framework to investigate the parallels and differences in meaning, usage, and semantic expansion between the two languages. The data indicate that samui pertains to an unpleasant and frequently intolerable body sensation induced by low temperatures, but tsumetai signifies the physical coldness of inanimate objects like water or air and might figuratively extend to characterize an individual's demeanor or disposition. In Javanese, adhem represents a cool temperature in the air or food and beverages, atis represents a cold sensation linked to air and precipitation, and anyep pertains to a wider semantic domain that includes cold sensations experienced through things and figuratively conveys a bland or insipid flavor. Conversely, samui semantically coincides with atis, whereas tsumetai aligns with adhem and anyep. The research indicates that metaphorical expansions of cold to characterize personality exist in Japanese but not in Javanese, while the link between coldness and insipid flavor is exclusive to Javanese. These findings emphasize cross-linguistic variations in the semantic conception of temperature-related adjectives and enhance contrastive linguistics and semantic research.